EXPLORING TRANSLANGUAGING IN EFL CLASSROOM COMMUNICATION: INSIGHTS FROM LECTURERS' EXPERIENCES IN INDONESIA - Helena Badu (Adisam Publisher, 2025)
This study explores translanguaging practices in English as a Foreign Language (EFL) classroom communication based on the experiences and perspectives of three English Language Education Study Program (ELESP) lecturers from Universitas Negeri Gorontalo in Indonesia. Translanguaging, which involves the strategic use of students' native language alongside the target language, aims to enhance student comprehension in EFL learning. Using a qualitative descriptive approach, the study finds that translanguaging strengthens students' understanding, confidence, and participation, particularly when dealing with complex material. However, challenges arise in balancing the use of English and the native language, as over-reliance on the native language may hinder long-term English fluency. This research contributes to understanding the effects of translanguaging in EFL teaching in Indonesia and provides recommendations for educational practitioners.